Bilateral endobronchial metastases from prostate cancer: A case report with literature review. (2020) - Jin, Caibao; Ren, Hui; Hu, Yang; Wu, Jingyi; Hu, Yanping; Wang, Zhijun; Wei, Youying; Yang, Bin; Yang, Ling
Abstract: Endobronchial metastases from prostate cancers are a rare phenomenon with only limited cases reported to date. Bronchoscopic biopsy and immunohistochemical test are essential for determining the diagnosis. And serum PSA level is a significant biomarker to assist the diagnosis. Our case describes a 68-year-old man presenting with bilateral endobronchial metastases after 5 years disease-free survival of prostate cancer.